(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2016)
The purpose of this study is to understand which textual skills children appropriate in interactive situations with science communication texts. For this, oral and written texts were analyzed where children expressed their understanding about a scientific concept. The theoretical and methodological perspective of the analysis draws on the Bakhtin’s conceptions of verbal interaction and in the micro genetic analysis. Scenes of work from science classes were recorded. The participants were 9-10 years-old children who attended the 4th year of a public elementary school in Belo Horizonte. The analysis of both the episodes and the texts produced by the children showed that the interaction with science communication texts provided to children starting to read an opportunity to appropriate textual skills reflected on the speech and writing during a science class to be closer to the knowledge produced from science communication texts. However, it was observed that such process does not occur spontaneously, since it is necessary that the educational context provides support to work with the language, instead of only talking about it. Therefore, science communication texts may enable to express the knowledge, the appropriation of strategies and textual skills along with the ability of using an explanatory language.